2013
DOI: 10.1021/ac3023982
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Signal Amplification for Sensitive and Real-Time Fluorescence Anisotropy Detection of Small Molecules

Abstract: Fluorescence anisotropy (FA) is a reliable, sensitive, and robust assay approach for determination of many biological targets. However, it is generally not applicable for the assay of small molecules because their molecular masses are relatively too small to produce observable FA value changes. To address this issue, we report herein the development of a FA signal amplification strategy by employing graphene oxide (GO) as the signal amplifier. Because of the extraordinarily larger volume of GO, the fluorophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 46 publications
6
77
0
Order By: Relevance
“…16C-TMR-A25 and 23A-TMR-A25 can be used as a pair of aptamer probes for FA sensing, showing complementary FA response to ATP. The obtained sensitivity for ATP analysis in this work is comparable to that obtained in many aptamer-based FA assays and fluorescence assays for ATP (Cui et al, 2012;Feng et al, 2014;Juskowiak, 2011;Liu et al, 2009Liu et al, , 2013Sassolas et al, 2011;Zhu et al, 2012).…”
Section: Fa Sensing Atpsupporting
confidence: 81%
See 1 more Smart Citation
“…16C-TMR-A25 and 23A-TMR-A25 can be used as a pair of aptamer probes for FA sensing, showing complementary FA response to ATP. The obtained sensitivity for ATP analysis in this work is comparable to that obtained in many aptamer-based FA assays and fluorescence assays for ATP (Cui et al, 2012;Feng et al, 2014;Juskowiak, 2011;Liu et al, 2009Liu et al, , 2013Sassolas et al, 2011;Zhu et al, 2012).…”
Section: Fa Sensing Atpsupporting
confidence: 81%
“…proteins and oligonucleotides) or nanomaterials (e.g. gold nanoparticles, graphene, and silica nanoparticles) have been introduced in assay development by increasing the binding-induced molecular weight change (Cruz-Aguado and Penner, 2008;Cui et al, 2012;Huang et al, 2012;Liu et al, 2013;Ye, and Yin 2008;Yu et al, 2013;Zhu et al, 2011Zhu et al, , 2012 Recently, we have reported a simple and noncompetitive FA strategy for a small molecule, ochratoxin A, by using a TMR-labeled aptamer. (Zhao et al, 2014) It is based on the target-binding induced change of intramolecular interactions between TMR and the guanine (G) bases of the aptamer.…”
Section: Introductionmentioning
confidence: 99%
“…31−34 The comparison in assay performance with other FA assays for OTA and aptamer-based FA assays for small molecules is summarized in Table S4 in the Supporting Information. [25][26][27][28][29][31][32][33][34]57,58 ■ CONCLUSION In summary, we demonstrated a simple fluorescence anisotropy strategy for direct analysis of a small molecule, OTA, with a TMR-labeled anti-OTA aptamer. It relied on the changes of the intramolecular interaction between TMR and guanine bases of aptamer and the subsequent local rotation of TMR upon target binding.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…One reported FA assay for small molecules relies on the binding-induced structure switch of the aptamer with an end-labeled dye (e.g., fluorescein or Texas red) and the subsequent change of the local rotation of the fluorescent dye, but only small FA increase is observed in most of cases. 25,26 Mass amplifying strategies recently have been exploited by using DNA oligos, 27−29 DNA-binding proteins (e.g., single-stranded DNA binding (SSB) protein and thrombin), 30−32 or nanomaterials 33,34 to improve the fluorescence anisotropy response by increasing the change of the molecular size of the aptamer upon binding of small-molecule targets. In these approaches, competitive displacement or structure switching is usually involved.…”
mentioning
confidence: 99%
“…Using this method, ATP was detected down to 1 μM. Importantly, the detection could be achieved in human serum samples [77].…”
Section: Fluorescence Anisotropy Based Assaysmentioning
confidence: 97%